The Influence of Product Knowledge and TikTok Beauty Influencers on Purchasing Decisions of Wardah Glating Liquid Lip with the Intention to Buy As Intervening Variables - Rini, Listya; Ervina Indiworo, Rr Hawik; Meiriyanti, Rita (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research examines the influence of product knowledge, TikTok beauty influencers on purchasing decisions with purchase interest as an intervening variable. This research was conducted using quantitative methods, the population of this study were consumers who had purchased Wardah glasting liquid lip products in Semarang City. This research uses a non-probability sampling technique, namely Accidental Sampling and takes data from 95 respondents collected. The data collection method in this research uses a questionnaire with SEM (Structural Equation Modeling) analysis techniques on SmartPLS 3.29 software as a tool in research analysis. The research results show that product knowledge and TikTok beauty influencers have a positive effect on purchasing interest. The variables of product knowledge and TikTok beauty influencers have a positive and significant effect on purchasing decisions. Product knowledge and TikTok beauty influencers have a positive influence on purchasing decisions which are mediated by purchasing interest.